2021
DOI: 10.48550/arxiv.2102.02449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Fornax3D project: Assembly histories of lenticular galaxies from a combined dynamical and population orbital analysis

A. Poci,
R. M. McDermid,
M. Lyubenova
et al.

Abstract: In order to assess the impact of the environment on the formation and evolution of galaxies, accurate assembly histories of such galaxies are needed. However, these measurements are observationally difficult owing to the diversity of formation paths that lead to the same present-day state of a galaxy. In this work, we apply a powerful new technique in order to observationally derive accurate assembly histories through a self-consistent combined stellar dynamical and population galaxy model. We present this app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 166 publications
(150 reference statements)
1
4
0
Order By: Relevance
“…In Fahrion et al (2019b), we argued that the old age and high metallicity of the NSC in FCC 47 indicates an efficient formation at early times. Similar arguments were made in the detailed analysis of FCC 170 by Pinna et al (2019a) using the same F3D MUSE data which showed that FCC 170 assembled very rapidly and efficiently at early times (see also Poci et al 2021). Their SFH of the central region of FCC 170 is similar to the one presented here.…”
Section: Most Massive Galaxiessupporting
confidence: 86%
See 2 more Smart Citations
“…In Fahrion et al (2019b), we argued that the old age and high metallicity of the NSC in FCC 47 indicates an efficient formation at early times. Similar arguments were made in the detailed analysis of FCC 170 by Pinna et al (2019a) using the same F3D MUSE data which showed that FCC 170 assembled very rapidly and efficiently at early times (see also Poci et al 2021). Their SFH of the central region of FCC 170 is similar to the one presented here.…”
Section: Most Massive Galaxiessupporting
confidence: 86%
“…Lower-mass edge-on S0 galaxies FCC 153 and FCC 177 are edge-on S0 galaxies like FCC 170, but at significantly lower galaxy mass (see e.g. Pinna et al 2019b;Poci et al 2021 for a detailed analysis using the F3D MUSE data). Pinna et al (2019b) and the Voronoi binned radial profiles presented in this work generally find young ages toward the galaxy centres.…”
Section: Most Massive Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The merger of NGC 1380 with its most massive satellite occurring ∼ 10 Gyr ago is consistent with this scenario. Two other early-type galaxies in the same clump, NGC 1380A (FCC 177) and NGC 1381 (FCC 170), have also been suggested to have accreted a substantial fraction of stars ∼ 9 Gyr ago (Pinna et al 2019b,a;Poci et al 2021). On the other hand, for NGC 1427 and considering that the merger process could last for 1 − 2 Gyr, the constraint from the stellar age distribution of its hot inner stellar halo does allow the inferred merger event to have started before infall.…”
Section: Timing Of the Past Major Mergersmentioning
confidence: 99%
“…Stellar orbits in the model have been further colored with age and metallicities in a recently-developed population-orbit superposition method (Poci et al 2019;Zhu et al 2020). By fitting the stellar kinematic, age and metallicity maps simultaneously, we have been able to obtain the internal stellar orbit distribution as well as the age and metallicity distributions (Poci et al 2021). With this novel method, chemo-dynamically identification of galactic structures as employed in the Milky Way, has become possible for external galaxies.…”
Section: Introductionmentioning
confidence: 99%